PERENCANAAN REKRUTMEN SDM DARI TENAGA HONORER KATEGORI II MENJADI CPNS DI KABUPATEN PEMALANG - Priyo Utomo; Mardiyono .; Siti Rochmah (REFORMASI, 2015)
Motivated by the regional autonomy era which authorizes local governments to take care of their household including human resources management authority in order to produce professional civil servants. Therefore, a change in civil servants management policy is needed including recruitment planning. This study aims to describe and analyze the planning of human resource recruitment of temporary employees category II into CPNS in Pemalang Regency, the supporting and inhibiting factors in the planning of human resources recruitment of temporary employees category II into CPNS in Pemalang Regency. The method used is qualitative with descriptive approach. The data was analyzed using interactive analysis model from Miles and Huberman. The results showed that the planning of human resources recruitment of temporary employees category II into CPNS in Pemalang Regency does not comply with the steps of recruitment and the applicable provisions because it was not based on job analysis; the supporting factors are budget and regulation, while the inhibiting factors are the personnel information systems, human resources, central government policies, coordination among government agencies in Pemalang Regency